Evaluation of Mother-Child Agreement and Factorial Structures of the SCARED Questionnaire in an Italian Clinical Sample - Scaini, Simona; Ogliari, Anna; De Carolis, Ludovica; Bellodi, Laura; Di Serio, Clelia; Brombin, Chiara (Frontiers in Psychology, 2017)
BACKGROUND: A great part of the literature has confirmed the importance of both child and parents reports as source of factual information, especially for childhood emotional syndromes. In our study we aimed at: i) calculating mother-child agreement and ii) evaluating factorial structure of the Screen for Child Anxiety Related Emotional Disorders (SCARED) questionnaire in an Italian clinical sample. under, Social Phobia and School Phobia. The novelty of this contribution is twofold: first, from a clinical point of view, we investigated the parent-child agreement level and examined separately the factorial structures of both parent and child versions of the SCARED for the first time in an Italian clinical sample. Second, unlike previous studies, we used statistical approaches specifically suited to account for the ordinal nature of the collected variables. METHOD: In a clinical sample of 171 children and adolescents aged 8–18 and their mothers we evaluated inter-rater agreement using weighted kappa indices to assess agreement for each item belonging to a certain SCARED subscale. Exploratory factor analysis for ordinal data was then performed on the polychoric correlation matrix calculated on SCARED items. Differences in the numbers of symptoms reported by children and parents were evaluated as well. RESULTS and CONCLUSIONS: Our results reveal moderate to strong mother-child agreement. A significant age effect is present. Two different factorial solutions emerged for parent and child SCARED versions (a 5 factor structure for parents and a 6 factor solution in the child version, including a factor on “Worry about Parents”). This study confirmed the importance of evaluating both child and parent reports in assessment protocols for anxiety disorders. Our findings could help clinicians to determine which information, and from which rater, must be accounted for in evaluating treatment decisions. Moreover, we find that patients characteristics, such as gender and age, should be taken into account when assessing agreement.